14-bit ADC as voltage monitoring device for power supply module 6 using I2C interface - Edison R. Castillo; Catherine D. Samson; Glenn N. Ortiz; Mark Joseph B. Enojas (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Thereare recorded downtime in the current testing processes of microelectronic packages. The available test equipment, the isolation of the power supply modules and the processes of testing must be changed in order to minimize the downtime. This study presents the design and development of a voltage monitoring device made of a 14-bit analog to digital converter (ADC) interfaced through inter-integrated circuit (I2C) for power supply module 6 (PS6). It is built to address the downtime in isolation and testing process of PS6. This setup is able to monitor and display three output voltages operating in 4-12V signals through athin film transistor (TFT) monitor. Tests were conducted for the nominal voltage and current setting scalled the three-point tests. In result, the fault detection and calibration process of PS6 are able to minimize downtimes. The developed voltage monitoring device has an acceptable percentage of 0.04572% which also canbe a replacement for digital multimeters (DMMs) for specific applications to PS6.